1990
DOI: 10.1525/aa.1990.92.2.02a00030
|View full text |Cite
|
Sign up to set email alerts
|

Women, Religion, and Modernization: Tradition and Transformation among Elderly Jews in Israel

Abstract: Modernization affects the religious lives of women in diverse and dramatic ways. On the one hand, women may find increased arenas for religious involvement, both inside and outside of traditional religious frameworks. Simultaneously, women's rituals and beliefs are often especially vulnerable to attacks from the forces of modernization. This paper focuses on the experience of elderly Jewish women of Asian origin who now live in modern Israel. The author suggests that the very nature of women's religion—domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…For example, the "new" moral code discusses the love and respect for one's spouse and family (as does the old), but it is the strict behavioral regulations which, especially from the perspective offered by women, imply an improvement in their own lives. Studies report the positive effects that conversion seems to have on women, either by allowing them access to literacy (Sered 1990), compensating for loss of prestige, as with Navajo women (Blanchard 1975), providing advice, and, as in our case, by restricting alcohol consumption and polygyny in Guatemala (Bossen 1984). The apparent freedom of Catholics "to do whatever one wants" often translates into freedom to drink, to womanize, to misbehave, according to Protestants.…”
Section: Specific and General Codes Of Lifementioning
confidence: 77%
“…For example, the "new" moral code discusses the love and respect for one's spouse and family (as does the old), but it is the strict behavioral regulations which, especially from the perspective offered by women, imply an improvement in their own lives. Studies report the positive effects that conversion seems to have on women, either by allowing them access to literacy (Sered 1990), compensating for loss of prestige, as with Navajo women (Blanchard 1975), providing advice, and, as in our case, by restricting alcohol consumption and polygyny in Guatemala (Bossen 1984). The apparent freedom of Catholics "to do whatever one wants" often translates into freedom to drink, to womanize, to misbehave, according to Protestants.…”
Section: Specific and General Codes Of Lifementioning
confidence: 77%
“…The more complex society steps in and replaces these social roles with professionals such as doctors, governmentappointed chiefs, teachers, missionaries, and wageworkers. Sered (1990) reported that social roles and family structure were changed during the process of modernization in Colombia:…”
Section: Literature Reviewmentioning
confidence: 99%
“…The stress that women experience depends on the social roles women play in the modern economy and their involvement with their husband's family and kin rather than on modern attitudes or modern economic participation (Weisner & Abbott, 1975). Sered (1990) suggested that modernization in any society has a paradoxical effect on women's lives and religion. Modernization opens up new opportunities for women in male-dominated religious ceremonies.…”
Section: Modernization and Stressmentioning
confidence: 99%
See 2 more Smart Citations